Identidade feminina, família e profissão: a experiência de ser mulher na contemporaneidade - Pinto, Virgínia Cavalcanti (2005)
This is a qualitative research, adopt the perspective of psyche-social-cultural studies and has the objective to comprehend the experience to be a woman nowadays in front of the professional world solicitations and family's life, which has been guided through the ethic of excellence. The comprehension about the theme, has began according to analyses of six women testimonies, tree marriage and three singles, they integrate a medium social level and professionally actives. Their words reveal feelings, contradictions, believes and aspirations that show to us how they have been experienced their female identity. Their testimonies were taped and after literally transcribe. The considerations made about the analyses showed, besides others aspects, that: the actual woman understands that as in a familiar atmosphere as in a professional atmosphere, both sides been part of their lives together, hadn't been reason to opt for to live one side only. The profession has been seen like the realization of a work for affinity, but like the obtainable of a good remuneration. The exigency, as in profession as in domestic atmosphere, get the actual woman reconfigured their relations with the other people in a general form, above all, with that composed her families, has made changed how she represent her familiar role. She shows herself in a multiple forms, bringing in herself a diversity of posture that, in the same time, it's impossible the conception and riches her possibilities to be